2007
DOI: 10.1080/00016340701322085
|View full text |Cite
|
Sign up to set email alerts
|

VNTR I/I genotype of insulin gene is associated with the increase of follicle number independent from polycystic ovary syndrome

Abstract: We suggest that INS VNTR genotypes are not associated with PCOS in general, but could have a certain influence on the phenotypic spectrum of the syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…This indicated the presence of a certain relationship between anovulation and insulin related genes. Kadri et al [24] also observed that the mean ovarian follicle number was lower in VNTR I/III and III/III individuals compared to VNTR I/I individuals, while Michelmore et al [35] also declared that both III/III genotype and paternal class III allele transmission were significantly related to the increased number of PCOS features and to reduced insulin sensitivity among women with PCO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated the presence of a certain relationship between anovulation and insulin related genes. Kadri et al [24] also observed that the mean ovarian follicle number was lower in VNTR I/III and III/III individuals compared to VNTR I/I individuals, while Michelmore et al [35] also declared that both III/III genotype and paternal class III allele transmission were significantly related to the increased number of PCOS features and to reduced insulin sensitivity among women with PCO.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 13 case-control studies [21][22][23][24][25][26][27][28][29][30] including 1,767 cases and 4,181 controls, were included in the analysis. Waterworth DM [21] and Powell BL [23] were conducted on the anovulatory PCOS.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…The included studies were limited to those conforming to HWE and those with high NOS score (P7). Three studies [10,14,18] with relatively low NOS score (<7) and one study [10] being not in agreement with HWE (P < 0.05) were excluded. The corresponding pooled ORs were not materially altered indicating that our results were robust (Table 2).…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Our initial search identified a total of 476 potentially eligible articles. Based on our inclusion criteria, a total of 8 articles were involved in this meta-analysis [10,[12][13][14][15][16][17][18]. There was perfect inter-rater reliability for the selection of studies to be included in the meta-analysis, with Kappa values of 0.834 based on titles and abstracts and 0.857 based on full texts.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation